中国农业剩余劳动力转移问题研究 = A study of the transfer of agricultural surplus labor in China - 催征 Cui, Zheng (2008)
This paper comprehensively analyzes the transfer problem of China’s agricultural surplus labor with relevant classical development economic models, like Lewis’s dual economic structure model, Fei and Ranis model, and Todaro’s urban-rural migration model. However, due to the special characteristics of China’s agricultural surplus labor, these classical models are not completely suitable for China.